Pengaruh Bauran Pemasaran dan Fasilitas terhadap Loyalitas Konsumen Kafe Day Coff Cifest Kecamatan Cikarang Selatan - Zahran, Wahidin Septa; Putriani, Oktavina Dwi (JAMBIS : Jurnal Administrasi Bisnis, 2024)
This study aims to analyze the phenomenon of decreasing the number of loyal consumers in the Day Coff Cifest Cafe located in South Cikarang District.This phenomenon is a major concern because loyal consumers have a crucial role in maintaining business stability and making a positive contribution to company sustainability.The decline in the number of loyal consumers can be caused by changes in consumer trends, business competition, shifts in market preferences, or even the impact of the economic crisis. Therefore, this study will focus on identifying the main causes of declining consumer loyalty and its impact on business performance.The research method used is a quantitative method involving a consumer survey of 98 respondents who are loyal consumers of Day Coff Cifest Cafe Cikarang Selatan and the analysis of historical sales data.The results of this study show that the Marketing Mix has a significant and positive effect on Consumer Loyalty by 24.5%. Facilities have a significant and positive effect on Consumer Loyalty by 26.1%. Both Marketing Mix and Facility has a significant and positive effect on Consumer Loyalty by 32.1%. This research is expected to provide in-depth insight into factors affecting consumer loyalty, strategies that can be implemented to maintain or increase the number of loyal consumers, suggestions to improve business competitiveness,giving contribution to stakeholders at Day Coff Cifest Cafe Cikarang Selatan in developing more effective and sustainable marketing strategies. In addition, the results of the research can be the foundation for the development of corporate policies that are more adaptive to the changes in market dynamics and consumer needs.